Experimental study on heat recovery from exhaust gas of chimneys using multi-tube tank: Effect of changing the head shape - Hassan Jaber; Amal Herez; Thierry Lemenand; Mohamad Ramadan; Mahmoud Khaled (International Journal of Thermofluids, 2023)
This paper presents a heat recovery system (HRS) that exploits the chimney`s exhaust gasses to heat water. Optimization of a waste HRS called the ''multi tube tank,'' as suggested by Khaled et al., is performed through experimental means. The design is described in detail and constructed, after which it is tested. Investigation of the impact of altering the head shape on the performance of the system is performed by constructing two distinct heads, one cylindrical (Cyl) and one conical (Con). Results indicate that the conical head (ConH) outperforms the cylindrical head (CylH). Specifically, in 275 min, the water temperature increases to a maximum of 59 °C with the CylH, while the ConH can raise the water temperature to 68 °C. Moreover, in 400 min, the ConH system can augment the water temperature up to 80 °C. Furthermore, economic and environmental analyses are performed, which show that the ConH system can save approximately 16 $/month more than the CylH system when the system is exploited 140 times/month for 275 min. Additionally, the payback period for the ConH system is about half that of the CylH system (6 months). Finally, the ConH system can reduce emissions of CO2 gas by 2 tons/year more than the CylH system when utilized 140 times/month.